Abdominal Plication for Better Cosmetic Outcomes During Deep Inferior Epigastric Perforator Flap Breast Reconstruction. Issue 5 (June 2021) - Van Vliet, Austin; Girardot, Alexandra; Bouchez, Jonathan; Kumar, Ambuj; Dayicioglu, Deniz
Abstract : Background: Deep inferior epigastric perforator flap (DIEP) for breast reconstruction is a widely accepted technique for breast reconstruction. Secondary benefit of this technique is abdominal contour improvement. Because of direct access, abdominal plication can be performed at the time of abdominal closure. Our goal was to investigate if this addition affected the complications. Methods: A retrospective chart review was performed on all DIEP flap reconstructions performed by a single surgeon at a cancer center, from March 2011 through February 2020. Presence of abdominal plication, age, and body mass index were compared with reoperation due to abdominal wound or hernia, procedure length in minutes, and length of stay. The association between the dependent and independent variables for the unadjusted and adjusted analysis was performed using the binary logistic regression analysis. Results: Three hundred fifty-eight DIEP flaps performed on 233 patients for breast reconstruction were analyzed. Flap loss was 1.7%. Abdominal plication was performed in 178 flaps (49.7%) and not performed in 180 flaps (50.3%). Thirty-nine percent were immediate; 61% were delayed. The results did not show a statistically significant association between abdominal plication and the need to reoperate ( P = 0.3). Results from the adjusted analysis (age, body mass index) also did not show a significant association between the plication, need to reoperate, procedure duration, or hospital stay ( P = 0.4). Conclusions: Abdominal plication can improve cosmetic outcomes without increasing the duration of surgery, hospital stay, or reoperation rates due to abdominal complications. Therefore, it can be a valuable addition in DIEP flap breast reconstructions.